ТАЛАБАЛАРНИ ИЖТИМОИЙ ФАОЛ ШАХС ҚИЛИБ ШАКЛЛАНТИРИШ МОДУЛИ БЎЙИЧА ДАСТУРИНИ АМАЛГА ОШИРИШ ОМИЛЛАРИ - Алқаров, И.Ш. (SCIENCE and SOCIETY, 2022)
The article discusses the components of the model "Formation of students as socially active people". In accordance with the requirements of today, the program is aimed at developing each component, taking into account the rich spiritual heritage of our great ancestors.